Confirmation of iron emission lines and nondetection of TiO on the dayside of KELT-9b with MAROON-X - Kasper, David; Bean, Jacob L.; Line, Michael R.; Seifahrt, Andreas; Stürmer, Julian; Pino, Lorenzo; Désert, Jean-Michel; Brogi, Matteo (The astrophysical journal. Part 2, Letters, 2021)
We present dayside thermal emission observations of the hottest exoplanet KELT-9b using the new MAROON-X spectrograph. We detect atomic lines in emission with a signal-to-noise ratio of 10 using cross-correlation with binary masks. The detection of emission lines confirms the presence of a thermal inversion in KELT-9b’s atmosphere. We also use M-dwarf stellar masks to search for TiO, which has recently been invoked to explain the unusual Hubble Space Telescope WFC3 spectrum of the planet. We find that the KELT-9b atmosphere is inconsistent with the M-dwarf masks. Furthermore, we use an atmospheric retrieval approach to place an upper limit on the TiO volume mixing ratio of 10−8.5 (at 99% confidence). This upper limit is inconsistent with the models used to match the WFC3 data, which require at least an order of magnitude more TiO, thus suggesting the need for an alternate explanation of the space-based data. Our retrieval results also strongly prefer an inverted temperature profile and atomic/ion abundances largely consistent with the expectations for a solar composition gas in thermochemical equilibrium. The exception is the retrieved abundance of Fe+, which is about 1-2 orders of magnitude greater than predictions. These results highlight the growing power of high-resolution spectrographs on large ground-based telescopes to characterize exoplanet atmospheres when used in combination with new retrieval techniques.
Gesehen am 14.12.2021